Howard and Christine Watkins Visit Florence, Italy - Watkins, Howard::::::::: (1988)
Pauline Sahakian, Christine Watkins, Jim Frey, Leslie Prusia, and Jonica Bushman dining on homemade pasta and fine wine at Jim Frey's apartment